Outlining the therapeutic itineraries of children with disabilities in the professional health care subsystem - Andreia Chaves Farias; Evanira Rodrigues Maia; Milena Silva Costa; Maria Rosilene Cândido Moreira; Joseph Dimas de Oliveira; Antonio Germane Alves Pinto
ABSTRACT Objectives: to identify the outlining of therapeutic itineraries of families of children with disabilities in the professional health care subsystem. Methods: qualitative research carried out in two specialized services in the state of Ceará, with 41 family members interviewed using the life path technique and reports submitted to descending hierarchical classification and similitude analysis, with the help of the IRaMuTeQ software and the theoretical framework of health care systems. Results: the classes described the families' itineraries in five paths, related to faith, support structures, medical behaviors, professionals, and health services. The professional subsystem stood out as deficient in outlining the therapeutic itinerary for access to health care for children with disabilities, without promoting integration between services in the Care Network. Final considerations: the families' therapeutic itineraries showed homogeneous discourse with themes related to the care of professionals and spiritual aspects.